ANALISIS PERENCANAAN DAN PENGANGGARAN PENDIDIKAN DI KABUPATEN SOLOK SELATAN - Toto Sugiarto (PAKAR Pendidikan, 2014)
This research is aim to identify and also evaluate document about planning and budgeting of educational in regancy South of Solok and also formulate policy, program, activity of relevant educational so that can finish problems of education in regancy South of Solok. Data is used in this research is primary data and data of sekunder. Method analysis that is: method analyze classification of problem of educational, Analyze SWOT, and Analysis Planning and Budgeting of Education in the regancy South of Solok. Result of planning document analysis (educational RPJPD, education RPJMD, RKPD, Renstra and Renja of duty Education) and analysis budgeting document (KUA and APBD) in middle and elementary educational in regancy South of Solok, not yet followed compilation order pursuant with Law number 25/ 2004, about Systems Planning of National Development.